A new combination in the genus Siler (Apiaceae) for the Balkan flora - Conti, Fabio; Bartolucci, Fabrizio; Niketić, Marjan; Lakušić, Dmitar (Phytotaxa, 2016)
A recent molecular study (Banasiak et al. 2016) reconstructed the phylogeny of all the genera belonging to tribe Scandiceae Spreng. subtribe Daucinae Dumort., showing that the genus Laserpitium Linnaeus (1753: 248) is polyphyletic. Banasiak et al. (l.c.) split Laserpitium into 5 genera: Laserpitium L., Ekimia Duman & Watson (1999: 200), Laser Borkh. ex Gaertner, Meyer & Scherbius (1799: 244, 384), Siler Miller (1754: without pagination), Silphiodaucus (Koso-Poljansky 1916: 211) Spalik, Wojewódska, Banasiak, Piwczyński & Reduron in Banasiak et al. (2016: 578), and Thapsia Linnaeus (1753: 261).